2012
DOI: 10.9734/bjmmr/2012/1228
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of a Unani Formulation (Jawarish amla sada) on Cyclophosphamide-induced Toxicity in Tumour Bearing Mice

Abstract: FA wrote the protocol, performed the statistical analysis, and wrote the first draft of the manuscript. HR, MK and SA managed the literature searches. KB, HR and RAA managed the analyses of the study. SR designed the study, wrote the protocol and edited the first and final drafts of the manuscript. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The result of the pilot study on the dose of cyclophosphamide appropriate for the study is at variance with the 50 mg/Kg cyclophosphamide used in the study by Ahmad, Rashid, Bhatia et al (2012). All animals survived the experimental period.…”
Section: Discussionmentioning
confidence: 91%
“…The result of the pilot study on the dose of cyclophosphamide appropriate for the study is at variance with the 50 mg/Kg cyclophosphamide used in the study by Ahmad, Rashid, Bhatia et al (2012). All animals survived the experimental period.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, immunomodulatory and anti-mycobacterial activities of JAS available in the market have been reported. [3,4] Literature survey revealed that the formulation composition of the marketed formulation varies significantly in terms of the number as well as the percent component of ingredients. In order to have uniform quality as well as batch to batch consistency, there is an urgent need to have some reference standards for quality control and standardization of this formulation.…”
Section: The Formulation Includes Six Medicinal Herbs Namelymentioning
confidence: 99%
“…It is easily available and cheap. Retrolective survey of ancient literature and scientific studies revealed that amla ( Emblica officinalis ) is an antipyretic, hepato-protective, appetizer, anti-tussive, nervine tonic, antihemorrhagic, anti-inflammatory drug7 which strengthens the vital organs and stomach and enhances vision. It is also a good blood purifier which inhibits production of morbid balgham and sauda.…”
Section: Selection Criteria For Adjuvant Drugmentioning
confidence: 99%
“…Jawarish amla as an adjuvant therapy may increase the efficiency of DOTS therapy, reduce the number of drug resistance cases and side effects as well as reverse the consequences and rejuvenate body power. A recent study of Jawarish amla “showed potential to provide protection against toxic effects of cyclophosphamide in tumour bearing mice.”7 Thus a study using Jawarish amla, an Unani adjuvant compound formulation, has been undertaken to evaluate its efficacy in combating the side effects of ATT drugs, reversing the adverse consequences of DOTS therapy, boosting general immunity and facilitating a complete recovery from TB.…”
Section: Introductionmentioning
confidence: 99%